Perceptions of Cockpit Configurations: A Culture and Gender Analysis. Issue 1 (3rd April 2017) - Mehta, Rian; Rice, Stephen; Winter, Scott; Eudy, Morgan
ABSTRACT: Objective : With the advancement of technology in recent years the topic of autonomous, pilotless cockpits have emerged. The rhetoric of this article revolves around passenger perceptions and their willingness to fly on board such aircraft. Background : Although studies have been conducted to gauge similar consumer perceptions, this study compared 3 different 2-pilot configurations based on pilot gender to that of the autonomous or automated cockpit. These configurations included 2 male pilots, 1 male and 1 female pilot, and 2 female pilots. Method : 433 participants from India and the United States were recruited using Amazon's Mechanical Turk and responded to questions designed to measure consumer perceptions on the topic at hand. The study used Rice, Mehta, et al.'s (2015) willingness-to-fly scale to collect the data. Results : The results suggested that all participants were more willing to fly on board all 3 types of 2-pilot configurations as opposed to the autonomous cockpit. However, Indian male participants showed a decrease in willingness to fly on board the 2-female-pilot configurations as opposed to the other 2-human-pilot configurations. Additionally, U.S. participants were much less willing to fly on board the autonomous configuration as compared to their Indian counterparts. Conclusion : The findings suggest that all participants were least willing to fly on aircraft flown completely by an autopilot. Differences were also noted based on pilot gender.